Flutter in 7 days - Malhotra, Aman (Packt, 2019)
"You'll gain the confidence to build customized UI's for your own projects using Flutter. You'll work with its cool features and understand how to compose widgets, add animations, and make your apps interactive in 7 days by building them throughout the course. By the end of this course, you will be up-to-speed with Flutter development and will be able to build stunningly rich cross-platform applications with a single codebase."--Resource description page